The impact of practical training based on narrative nursing on the humanistic care ability of Chinese intern nurses - Dai, Lili; Han, Yuqin; Jiang, Qunhua; Ge, Wenxian; Zhao, Hong; Xu, Ping (Frontiers in Medicine, 2025)
ObjectiveImproving the humanistic care ability of intern nurses and fostering a deep-seated sense of compassion are crucial goals. In this study, we aimed to investigate the effect of practical training based on narrative nursing on the humanistic care ability of intern nurses.MethodsRetrospective analysis was conducted on intern nurses who received practical training based on narrative nursing (n = 70) or regular training (n = 70) for 6 months. The differences in humanistic care ability, empathy, professional values, professional identity, and satisfaction between the two groups were evaluated. The univariate logistic regression analysis was constructed to determine the influencing factors of humanistic care ability.ResultsCompared to those who received regular training, intern nurses who received practical training based on narrative nursing showed significant improvements in humanistic care ability, empathy, professional values, and professional identity (all p < 0.05). Additionally, intern nurses were highly satisfied with practical training based on narrative nursing. Univariate logistic regression analysis revealed that practical training based on narrative nursing was an influencing factor of humanistic care ability (p < 0.05).ConclusionPractical training based on narrative nursing can significantly improve the humanistic care ability, empathy ability, professional values, and professional identity of nursing interns.